Developing Descriptive Writing Graphic Organizers’ of the Students at the Eighth Grade of SMP Swasta Kristen Agios Nikolaus in 2022/2023 - Zega, Yudika; Harefa, Afore Tahir; Zebua, Elwin Piarawan; Telaumbanua, Yasminar Amaerita (Journal of Education Research, 2023)
Based on the preliminary data, it was found that students in SMP Swasta Kristen Agios Nikolaus were still unable to write descriptive texts.  This is because the media used by the teacher is only in the form of a table on a piece of paper and is less interesting. This research aims to develop a learning media in writing descriptive text in the form of Graphic Organizers (GOs). The method used in this research is Research and Development (R & D) using the ADDIE model. There are several procedures in the ADDIE model, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. Based on the results of the study, it was found that the graphic organizers media were declared "very feasible" after being validated by media experts and linguists with a percentage of 93%. Graphic organizers media were also tested on students through three stages, namely individual trials with 4 students, small group trials with 10 students and field trials with 20 students and the results obtained that graphic organizers media were "very practical" used by students in writing description text with a percentage of 89%. And from the results of the student test, it was found that the average score of students as a whole was 87%. In other words, graphic organizers media is effective to improve students' ability in writing descriptive text.  Based on the results of the study, it is concluded that GOs media is very valid, very practical, and effective to be used by students in SMP Swasta Kristen Agios Nikolaus, especially in writing descriptive text.